VIRTUAL EDUCATION OR VIRTUALITY OF EDUCATION - Nieto Göller, Rafael Andrés (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
Well known globalization and societies on going technical process also the appeal of massive augmentation of all technologies considered as Information and Communication Technologies, had allowed the on line education as an open and long distance option –nontraditional or conventional– and methodological offensive answer that is being used more often by countries to challenge each other, by their respective public and private policies, challenges related to universal right to education, flexibility and acquisition ease, that demographic growth demands towards traditional and life education systems. From its virtual education importance, due to its methodology variety and dynamics, getting a profile of universal remedy, yet it unclear strategy because of myths and prejudice that its relation to knowledge, being and language, offering to excluded and forgotten social groups wide access to opportunities, and to those whose needs of space or time are rather peculiar, in order to guarantee and improve education service quality by using technology developments into teaching and learning processes also stimulating innovation at and for education praxis as a whole and creating a new “virtual reality”; a new way to simulate in order to develop –education’s virtuality–.Our interest and aim in our proposal is to reflect and present the objective of origines, debates, influeces, interpretations and realities –from education institutes and context as human life as well– presented as opportunities for learning and knowledge construction and yet its eventual future.